Silicon-carbon composite negative electrode material containing lithium-rich long-chain composite salt and preparation method of silicon-carbon composite negative electrode material
By wrapping lithium-rich long-chain composite salt in the silicon-carbon composite anode material of lithium-ion secondary batteries, a salt-like bridge structure is formed, which solves the problems of lithium metal structure rupture and electrolyte side reaction, and achieves the extension of the battery cycle life and Improved efficiency.
Patent Information
- Application Number
- CN202310999828.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-09
- Publication Date
- 2025-02-18
AI Technical Summary
The prior art is difficult to effectively suppress the rupture of the lithium metal structure and the continuous side reaction of electrolytes in lithium-ion secondary batteries, resulting in a decrease in the battery cycle and Coulomb efficiency, and even short circuits and combustion.
Using silicon-carbon composite negative electrode material containing lithium-rich long chain composite salt, the lithium-rich long chain composite salt is wound on the surface of silicon-carbon composite particles to form a salt-type bridge structure, which enhances the Kulun cycle efficiency and stabilizes the overall silicon-carbon composite material. Configuration.
Effectively inhibit the rupture of lithium metal structure and the continuous side reaction of electrolytes, extend the cycle life of the battery, and improve the stability and efficiency of the battery.
Smart Images

Figure CN119481022A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a silicon-carbon composite negative electrode material containing a lithium-rich long-chain composite salt and a preparation method thereof. Background Art
[0002] Since the lithium metal negative electrode has the highest theoretical gram capacity (3860mAh*g-1) and the lowest electrochemical potential (-3.04V), it is currently regarded as the best choice for the negative electrode of lithium-ion secondary batteries. However, due to the high reactivity of lithium metal, it is easy to spontaneously form a heterogeneous and fragile solid electrolyte interface (SEI), and at the same time promote the growth of needle-shaped dendrites. The problem that follows is the rupture of the lithium metal structure and continuous side reactions with the electrolyte. The continuous side reactions will lead to a decrease in the battery cycle and coulomb efficiency, and ultimately cause battery short circuit and battery combustion. Therefore, how to effectively inhibit the growth of dendrites and thus extend the cycle life of the battery has become an important topic in the application and research field of lithium-ion secondary batteries. In the prior art, the method of stabilizing lithium metal includes: First, using liquid electrolyte additives to form a good quality SEI layer, which not only promotes the conduction of lithium ions but also protects the surface of the lithium metal electrode. However, this method of penetrating additives can only be used in liquid electrolytes, and cannot be effective for all-solid-state lithium-ion secondary batteries. Second, directly use oxide-related solid electrolytes as a physical barrier to protect the lithium metal surface and inhibit dendrite formation. However, since solid electrolytes with high ionic conductivity still need time to mature and process, and the compatibility between oxide electrolytes and lithium metal is very low, the above method cannot immediately become the mainstream in the industry. Summary of the invention
[0003] In view of this, it is indeed necessary to provide a silicon-carbon composite negative electrode material containing a lithium-rich long-chain composite salt and a preparation method thereof, which can solve the above-mentioned technical problems.
[0004] A silicon-carbon composite negative electrode material containing a lithium-rich long-chain composite salt, comprising:
[0005] A silicon-carbon composite material slurry, wherein the silicon-carbon composite material slurry comprises a plurality of silicon-carbon composite material particles, each of which comprises an element-doped silicon nanoparticle, a first carbon coating layer and a second carbon coating layer, wherein the element-doped silicon nanoparticle is a core, the first carbon coating layer is coated on the surface of the element-doped silicon nanoparticle, the second carbon coating layer covers the first carbon coating layer, and the doping element is one or more of a IIIA group element, a VA group element or a transition metal element;
[0006] A lithium-rich long-chain composite salt, wherein the lithium-rich long-chain composite salt comprises a plurality of composite ion bridging structures, each of which comprises a plurality of cations, a first anion group and a second anion group, wherein the first anion group and the second anion group form the composite ion bridging structure through the plurality of cations, and the plurality of cations comprises lithium ions.
[0007] The silicon-carbon composite material contains no silicon oxide at all or almost no silicon oxide.
[0008] The mass percentage of silicon oxide in the silicon-carbon composite material is less than or equal to 0.1%.
[0009] The cations include ammonium ions, lithium ions, and other metal ions.
[0010] The first anion group includes one or more of a carboxylic acid functional group (COOH), an amide functional group (CONH2), an ester functional group (COOR), a full / hemiacetal, a full / hemiketal, and a conjugate acid-base pair of the above groups.
[0011] The second anion group includes one or more of phosphate, carbonate, nitrate, nitrate and sulfate.
[0012] The silicon-carbon composite negative electrode material slurry further includes conductive carbon particles, and the conductive carbon particles include carbon black, Super P, Ketjen black and carbon nanotubes.
[0013] A method for preparing a silicon-carbon composite negative electrode material containing a lithium-rich long-chain composite salt comprises the following steps:
[0014] S1: preparing a silicon-carbon composite negative electrode slurry, wherein the silicon-carbon composite negative electrode slurry contains a silicon-carbon composite material;
[0015] S2: providing a high molecular polymer and a lithium salt, wherein the high molecular polymer includes a cation and a first anion group, and the lithium salt includes a second anion group;
[0016] S3: adding the lithium salt to the polymer, so that the lithium ions in the lithium salt and the first anion group and the second anion group form a bridging structure together to form a lithium-rich long-chain composite salt; and
[0017] S4: mixing the lithium-rich long-chain composite salt with the silicon-carbon composite negative electrode slurry to form the silicon-carbon composite negative electrode material containing the lithium-rich long-chain composite salt.
[0018] The cations include one or more of H+, Li+, Na+, K+, and NH4+.
[0019] The silicon-carbon composite negative electrode material containing lithium-rich long-chain composite salt provided by the present invention has the following advantages: the structure of salt bridges formed in the slurry can effectively enhance the coulomb cycle efficiency, and the overall configuration of the silicon-carbon composite material particles is stabilized by the long-chain polymer structure; because the lithium-rich long-chain composite salt generates salts with bridge structures, it has a better lithium replenishment effect and can replenish the dead lithium reduced by the cycle. At the same time, because the salts forming the bridge structure have a long-chain structure, the entire negative electrode material has better stability. The method of the silicon-carbon composite negative electrode material containing lithium-rich long-chain composite salt provided by the present invention has a simple process, is easy to control the process, and is suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 A schematic diagram of the structure in which a lithium-rich long-chain composite salt is wrapped around silicon-carbon composite material particles in a silicon-carbon composite negative electrode material containing a lithium-rich long-chain composite salt provided in an embodiment of the present invention.
[0021] Figure 2 A schematic diagram of the structure of silicon-carbon composite material particles provided in an embodiment of the present invention.
[0022] Figure 3 A schematic diagram of lithium-rich long-chain composite salts provided in an embodiment of the present invention being entangled with each other to form different long-chain structures.
[0023] Main component symbols
[0024] Silicon-carbon composite negative electrode material particles 10
[0025] Element-doped silicon nanoparticles 1 02
[0026] The first carbon coating layer 104
[0027] The second carbon coating layer 106
[0028] Doping elements 1 08
[0029] Lithium-rich long-chain composite salt structure 20
[0030] The following specific implementation manner will further illustrate the present invention in conjunction with the above-mentioned drawings. DETAILED DESCRIPTION
[0031] The silicon-carbon composite material and the preparation method thereof provided by the present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments. In the absence of conflict, the following embodiments and features in the embodiments may be combined with each other.
[0032] The embodiment of the present invention provides a silicon-carbon composite negative electrode material containing a lithium-rich long-chain composite salt. The silicon-carbon composite negative electrode material containing a lithium-rich long-chain composite salt comprises a plurality of silicon-carbon composite material particles and a lithium-rich long-chain composite salt. Figure 1The molecular structure of the lithium-rich long-chain composite salt 20 is a long chain, which can be wound around the surface of the silicon-carbon composite material particle 10 .
[0033] See also Figure 2 , the silicon-carbon composite negative electrode material particle 10 includes a silicon nanoparticle 102, a first carbon coating layer 104, a second carbon coating layer 106 and an elastic coating layer 108. The silicon nanoparticle 102 is a core, the first carbon coating layer 104 is coated on the surface of the silicon nanoparticle 102, the second carbon coating layer 106 coats the first carbon coating layer 104, and the elastic coating layer 108 coats the second carbon coating layer 106. The silicon nanoparticle 102 includes a silicon matrix (not labeled in the figure) and a doping element (not labeled in the figure) located in the silicon matrix. The doping element is one or more of group IIIA elements, group VA elements or transition metal elements.
[0034] The particle size of the silicon-carbon composite negative electrode material particle 10 is 10 microns to 20 microns. The shape of the silicon-carbon composite negative electrode material particle 10 can be spherical or quasi-spherical. The quasi-spherical shape means that its shape is close to a sphere, but not a strict sphere, and is an irregular shape. The particle size of the silicon nanoparticle 102 is 10 nanometers to 100 nanometers.
[0035] The doping element may be a IIIA group element, such as boron (B), aluminum (Al), gallium (Ga), indium (In), thallium (T1), germanium (Ge), tin (Sn) or lead (Pb); it may also be a VA group element, such as nitrogen (N), phosphorus (P), arsenic (As), tellurium (Sb) or bismuth (Bi); it may also be a transition metal element, such as scandium (Sc), titanium (Ti), vanadium (V), chromium (Cr), manganese (Mn), iron (Fe), cobalt (Co), nickel (Ni), copper (Cu), zinc (Zn), yttrium (Y), zirconium (Zr), niobium (Nb), molybdenum (Mo), technetium (Tc), ruthenium (Ru), rhodium (Rh), palladium (Pd), silver (Ag) or cadmium (Cd), etc. The element doping may reserve space in the silicon lattice, and when the silicon-carbon composite negative electrode material is used as the negative electrode, during the cycle, the doping element may provide the buffer space required for the volume expansion of the silicon material, thereby greatly improving the cycle performance of the silicon-carbon composite negative electrode material. Each silicon-carbon composite negative electrode material particle 10 may include only one doping element, or may include two or more doping elements.
[0036] In one embodiment, the silicon-carbon composite negative electrode material contains no silicon oxide or almost no silicon oxide.
[0037] In one embodiment, the mass percentage of silicon oxide in the silicon-carbon composite negative electrode material is less than or equal to 0.1%.
[0038] In a certain embodiment, the silicon-carbon composite negative electrode material contains no oxide or almost no oxide.
[0039] In one embodiment, the silicon-carbon composite negative electrode material particle 10 is composed of silicon nanoparticles 102 , a first carbon coating layer 104 , a second carbon coating layer 106 and an elastic coating layer 108 .
[0040] In one embodiment, the silicon-carbon composite negative electrode material is substantially free of oxides. Therefore, when the silicon-carbon composite negative electrode material is used as a negative electrode, during the charge and discharge cycle, there are no irreversible oxides to increase the consumption of lithium ions, thereby improving the efficiency of the battery.
[0041] The material of the first carbon coating layer 104 includes at least one of asphalt, graphite and graphene. The first carbon coating layer 104 encapsulates silicon nanoparticles inside, which can inhibit volume expansion and reduce volume effect. The material of the second carbon coating layer 106 includes at least one of carbon black, carbon nanotubes and carbon nanofibers. The second carbon coating layer 106 encapsulates the first carbon coating layer 104. The second carbon coating layer 106 has a higher conductivity than the first carbon coating layer 104, and the second carbon coating layer 106 can provide charge transfer to increase the capacity of the battery.
[0042] The material of the elastic coating layer 108 includes a conductive material and an organic compound matrix, and the conductive material is distributed in the organic compound matrix. The conductive material includes one or more of natural graphite, artificial graphite, intermediate phase spherical graphite, expanded graphite, graphene and carbon nanotubes. The organic compound includes one or more of polyvinyl pyrrolidone (PVP), polyvinyl alcohol (PVA), polyphthalamide (PPA), polyacrylic acid (PAA) and sodium dodecylbenzene sulfonate (SDBS). Preferably, the organic compound contains a carboxylic acid functional group (COOH), an amide functional group (CONH2) or an ester functional group (COOR). More preferably, the organic compound contains a carboxylic acid functional group (COOH).
[0043] The lithium-rich long-chain composite salt 20 includes cations, a first anion group and a second anion group, wherein the cations include lithium ions. The first anion group and the second anion group form the composite ion bridging structure through the plurality of cations. The plurality of cations can be only lithium ions, or can further include other cations other than lithium ions, such as one or more of H+, Li+, Na+, K+, and NH4+. The first anion group includes one or more of a carboxylic acid functional group (COOH), an amide functional group (CONH2), an ester functional group (COOR), a full / semiacetal, a full / semiketal, and a conjugate acid-base pair of the above groups. The second anion group includes one or more of a phosphate, a carbonate, a nitrate, a nitrate, and a sulfate.
[0044] The composite ion bridging structure is composed of a cation and a first anion group and a second anion group, wherein the cation is located in the middle, and the two ends are respectively connected to the first anion group and the second anion group to form a long chain bridging structure. Therefore, the lithium-rich long-chain composite salt 20 is a long chain structure. Figure 3 The molecules of the two long-chain lithium-rich composite salts 20 can also be entangled or twisted with each other to form a variety of secondary topological structures.
[0045] The silicon-carbon composite negative electrode material containing lithium-rich long-chain composite salt may further include conductive carbon particles, and the conductive carbon particles include carbon black, Super P, Ketjen black and carbon nanotubes.
[0046] The silicon-carbon composite negative electrode material containing a lithium-rich long-chain composite salt is a slurry. The solvent of the slurry can be an organic solvent or water, and the liquid can be a mixture of the two. The silicon-carbon composite negative electrode material containing a lithium-rich long-chain composite salt is prepared by a slurry mixing method.
[0047] The silicon-carbon composite negative electrode material containing lithium-rich long-chain composite salt provided by the present invention has the following advantages: the salt bridging structure formed in the mixed slurry can effectively enhance the coulomb cycle efficiency and stabilize the overall configuration of the silicon-carbon composite material particles by the long-chain polymer structure; since the lithium-rich long-chain composite salt generates salts with a bridging structure, it has a better lithium replenishment effect and can replenish the dead lithium reduced due to circulation. At the same time, since the salts forming the bridging structure have a long-chain structure, the entire negative electrode material has better stability.
[0048] The embodiment of the present invention further provides a method for preparing a silicon-carbon composite negative electrode material containing a lithium-rich long-chain composite salt, which comprises the following steps:
[0049] S1: preparing a silicon-carbon composite negative electrode slurry, wherein the silicon-carbon composite negative electrode slurry contains a silicon-carbon composite material;
[0050] S2: providing a high molecular polymer and a lithium salt, wherein the high molecular polymer includes a cation and a first anion group, and the lithium salt includes a second anion group;
[0051] S3: adding the lithium salt to the polymer, so that the lithium ions in the lithium salt and the first anion group and the second anion group form a bridging structure together to form a lithium-rich long-chain composite salt; and
[0052] S4: mixing the lithium-rich long-chain composite salt with the silicon-carbon composite negative electrode slurry to form the silicon-carbon composite negative electrode material containing the lithium-rich long-chain composite salt.
[0053] Hereinafter, each step of the silicon-carbon composite negative electrode material containing lithium-rich long-chain composite salt provided in the embodiment of the present invention will be introduced in detail.
[0054] S1: preparing a silicon-carbon composite negative electrode slurry, wherein the silicon-carbon composite negative electrode slurry contains a silicon-carbon composite material.
[0055] The step S1 specifically includes the following steps:
[0056] S11: providing a silicon-carbon composite negative electrode material, and sintering the silicon-carbon composite negative electrode material; and
[0057] S12: adding the sintered material to a solution containing one molecule of a compound to obtain a mixture; and
[0058] S13: adding a SEI modifier, a phosphate flame retardant and conductive particles to the above mixture, mixing evenly, and obtaining a silicon-carbon composite negative electrode slurry.
[0059] In step S11, the silicon-carbon composite negative electrode material includes a plurality of silicon-carbon composite negative electrode material particles. The structure of the silicon-carbon composite negative electrode material particles is the same as the structure of the silicon-carbon composite negative electrode material particles 20 described above. The silicon-carbon composite negative electrode material is in powder form. The sintering step of the silicon-carbon composite negative electrode material is carried out in a reducing atmosphere or a vacuum environment, and the sintering temperature is 500°C to 1200°C. In some embodiments, the reducing atmosphere includes a nitrogen-hydrogen mixture. Sintering under a reducing atmosphere can remove excessive functional groups on the surface, increase the density and integrity of the carbon substrate coating, and the reducing atmosphere can also prevent silicon from being oxidized (oxide-free). The sintering step can be beneficial to further reduce the specific surface area of the silicon-carbon composite negative electrode material particles, reduce the agglomeration phenomenon of the slurry mixing process, and introduce nitrogen atoms to produce NC bonds, which can effectively improve the electron adsorption force between nano-silicon and the supported carbon material, and can remove the functional groups on the surface of the material that are prone to lithium trapping.
[0060] In step S12, the molecular compound solution is obtained by dissolving the molecular compound in an organic solvent. The molecular compound includes one or more of polyvinyl pyrrolidone (PVP), polyvinyl alcohol (PVA), polyphthalamide (PPA), polyacrylic acid (PAA) and sodium dodecylbenzene sulfonate (SDBS). The molecular compound may contain a carboxylic acid functional group (COOH), an amide functional group (CONH2) or an ester functional group (COOR). The organic solvent includes one or more of diethylene glycol, N-methylpyrrolidone, polyethylene glycol, propylene glycol or dimethyl sulfoxide. The mass percentage concentration of the molecular compound solution is 1% to 10%.
[0061] In step S13, the SEI modifier may be one or more of LiNO3, Li3PO4, LiF, LiOH, LiTFSI or LiFSI. The conductive particles may be carbon black, Super P or Ketjen black.
[0062] S2: providing a high molecular polymer and a lithium salt, wherein the high molecular polymer includes a cation and a first anion group, and the lithium salt includes a second anion group.
[0063] In step S2, the high molecular polymer includes a first anionic group. The atomic mass of the high molecular polymer is between 103 and 109 Daltons. The first anionic group includes one or more of a carboxylic acid functional group (COOH), an amide functional group (CONH2), an ester functional group (COOR), a full / semiacetal, a full / semiketal and a conjugate acid-base pair of the above groups. The high molecular polymer contains cations, which can be H+. According to actual needs, the H+ in the high molecular polymer can be replaced by Li+, (must be) Na+, K+, NH4+. Therefore, the cations in the polymer include one or more of H+, Li+, Na+, K+, NH4+. The high molecular polymer can also act as a binder.
[0064] In step S2, the anion of the lithium salt is a second anion group, and the second anion group includes one or more of phosphate, carbonate, nitrate, nitrate and sulfate. The preparation method of the lithium salt includes: mixing and stirring lithium hydroxide with an acidic solution containing a second anion group under a controllable specific temperature and atmosphere, stirring until the temperature of the mixed solution no longer changes, that is, the reaction is completed, and then the solution after the reaction is extracted and purified to obtain lithium salt. The salts can be in solid or solution state as required, and may present different crystal forms due to process parameters. The specific temperature range is 15 to 55 degrees Celsius. The atmosphere is under a protective gas and normal pressure environment. In this embodiment, the protective gas is nitrogen.
[0065] S3: adding the lithium salt to the high molecular polymer, so that the lithium ions in the lithium salt and the first anion group and the second anion group form a bridging structure together to form a lithium-rich long-chain composite salt.
[0066] In step S3, the polymer and the lithium salt are mixed to form a lithium-rich long-chain composite salt. After mixing, the first anion group in the polymer, the second anion group in the lithium salt and the cation in the mixed solution form a bridging structure, wherein the cation is located in the middle position, and the first anion group and the second anion group are connected at both ends to form a long-chain bridging structure. Therefore, the molecular structure of the lithium-rich long-chain composite salt is a long-chain structure.
[0067] S4: mixing the lithium-rich long-chain composite salt with the silicon-carbon composite negative electrode slurry to form the silicon-carbon composite negative electrode material containing the lithium-rich long-chain composite salt.
[0068] In step S4, after the long-chain lithium-rich long-chain composite salt is added, it is stirred evenly. The lithium-rich long-chain composite salt will wrap around the silicon-carbon composite material particles to fix the physical structure, form a composite ion bridge and form a solid electrolyte interface rich in lithium ions to stabilize the interface chemical properties. This interface has both the long-chain physical structure protection and the chemical stability of multi-functional groups.
[0069] After the silicon-carbon composite negative electrode material containing lithium-rich long-chain composite salt is prepared, the silicon-carbon composite negative electrode material containing lithium-rich long-chain composite salt can be further coated, rolled and dried to obtain a silicon-carbon composite negative electrode that can inhibit cyclic expansion.
[0070] In this embodiment, a silicon-carbon composite negative electrode material, a conductive agent and a binder with a mass percentage of 93:1:6 are dissolved in a solvent to obtain a mixture, and the solid content is controlled at 50%, and stage mixing is performed. The finished slurry is applied to the copper foil at a thickness of 50-200um at a speed of 0.1 cm / s, and then placed in a 50-100 degree Celsius oven for 10 minutes. After rolling to a specific thickness, the electrode pieces of a fixed area are cut out, and the conductivity is measured and SEM observation is performed to check the specifications. The qualified negative electrode pieces and ternary positive electrode pieces are mixed with 1mol / L LiPF6 / EC+DMC+EMC (v / v=1:1:1) electrolyte and Celga using conventional production processes.
[0071] rd 2400 separator for soft pack battery stack and 5Ah assembled battery for electrical specification testing.
[0072] First efficiency test: The negative electrode and lithium metal are assembled into a half-cell. After the assembly is completed and placed for 24 hours, a cyclic charge and discharge test is performed. The battery is first half-full (3.6V) and then degassed, and then charged to 4.3V; then the first discharge is performed to 3.0V, and the first coulomb efficiency is calculated. Then the cycle is performed at 1C to calculate the capacity retention rate. The comparative test results are shown in Tables 1 and 2.
[0073] Table 1
[0074]
[0075]
[0076] Table 2
[0077]
[0078] Cycle test: The negative electrode and the ternary positive electrode are assembled into a full battery. After the assembly is completed and placed for 24 hours, a cycle charge and discharge test is performed. The battery is first half full (3.6V) and then degassed, and then charged to 4.3V; then the first discharge is performed to 3.0V, and the first coulomb efficiency is calculated. Then the cycle is cycled 100 times at 1C, and the coulomb efficiency of each cycle is calculated. The comparative test results are shown in Table 3.
[0079] Table 3
[0080]
[0081] It can be seen from Tables 1 and 2 that when the negative electrode is prepared using the silicon-carbon composite negative electrode material containing the lithium-rich long-chain composite salt provided by the embodiment of the present invention, the battery has a higher first-round efficiency. The first coulomb efficiency shows that the first efficiency of the battery material using the lithium-rich long-chain composite salt is better than that of the general control group, indicating that the composite layer has achieved the effect of inhibiting decay. The long cycle retention rate indicates that the long-chain composite structure has the effect of stabilizing the structure of the silicon-carbon material. In the future, a variety of salt additives can be tried in this direction, or different types of modifications can be made to the long-chain functional machines, in order to improve the overall physical and chemical properties of the negative electrode.
[0082] It is understandable that the step numbering is intended to clearly describe the specific preparation method, and is not intended to limit the order of the steps.
[0083] The above description is some specific implementation methods of the present application, but it cannot be limited to these implementation methods in the actual application process. Those skilled in the art may also make other changes within the spirit of the present invention. Of course, these changes made according to the spirit of the present invention should be included in the scope of protection claimed by the present invention.
Claims
1. A silicon-carbon composite negative electrode material containing a lithium-rich long-chain composite salt, the improvement of which comprises: A silicon-carbon composite material slurry, wherein the silicon-carbon composite material slurry comprises a plurality of silicon-carbon composite material particles, each of which comprises an element-doped silicon nanoparticle, a first carbon coating layer and a second carbon coating layer, wherein the element-doped silicon nanoparticle is a core, the first carbon coating layer is coated on the surface of the element-doped silicon nanoparticle, the second carbon coating layer covers the first carbon coating layer, and the doping element is one or more of a IIIA group element, a VA group element or a transition metal element; A lithium-rich long-chain composite salt, wherein the lithium-rich long-chain composite salt comprises a plurality of composite ion bridging structures, each of which comprises a plurality of cations, a first anion group and a second anion group, wherein the first anion group and the second anion group form the composite ion bridging structure through the plurality of cations, and the plurality of cations comprises lithium ions.
2. The silicon-carbon composite negative electrode material containing a lithium-rich long-chain composite salt according to claim 1, characterized in that: The silicon-carbon composite material does not contain silicon oxide.
3. The silicon-carbon composite negative electrode material containing a lithium-rich long-chain composite salt according to claim 1, characterized in that: The cations include ammonium ions, hydrogen ions, lithium ions, and other metal ions.
4. The silicon-carbon composite negative electrode material containing a lithium-rich long-chain composite salt according to claim 1, characterized in that: The first anion group includes one or more of a carboxylic acid functional group (COOH), an amide functional group (CONH2), an ester functional group (COOR), a full / hemiacetal, a full / hemiketal, and a conjugate acid-base pair of the above groups.
5. The silicon-carbon composite negative electrode material containing a lithium-rich long-chain composite salt according to claim 1, characterized in that: The second anion group includes one or more of phosphate, carbonate, nitrate, nitrate and sulfate.
6. The silicon-carbon composite negative electrode material containing a lithium-rich long-chain composite salt according to any one of claims 1 to 5, characterized in that: The composite ion bridging structure is composed of a cation, a first anion group and a second anion group, wherein the cation is located in the middle, and the two ends are respectively connected to the first anion group and the second anion group to form a long chain bridging structure.
7. The silicon-carbon composite negative electrode material containing a lithium-rich long-chain composite salt according to claim 6, characterized in that: The molecular structure of the lithium-rich long-chain composite salt is a long chain, which is wound around the surface of the silicon-carbon composite material particles.
8. A method for preparing a silicon-carbon composite negative electrode material containing a lithium-rich long-chain composite salt, comprising the following steps: S1: preparing a silicon-carbon composite negative electrode slurry, wherein the silicon-carbon composite negative electrode slurry contains a silicon-carbon composite material; S2: providing a high molecular polymer and a lithium salt, wherein the high molecular polymer includes a cation and a first anion group, and the lithium salt includes a second anion group; S3: adding the lithium salt to a polymer so that the lithium ions in the lithium salt and the first anion group and the second anion group form a bridging structure together to form a lithium-rich long-chain composite salt; and S4: mixing the lithium-rich long-chain composite salt with a silicon-carbon composite negative electrode slurry to form the silicon-carbon composite negative electrode material containing the lithium-rich long-chain composite salt.
9. The method for preparing a silicon-carbon composite negative electrode material containing a lithium-rich long-chain composite salt according to claim 8, characterized in that: Step S1 includes: Providing a silicon-carbon composite negative electrode material, and sintering the silicon-carbon composite negative electrode material; and adding the sintered material into a solution containing a molecule of a compound to obtain a mixture; Add the SEI modifier, the phosphate flame retardant and the conductive particles into the above mixture, mix them evenly, and obtain the silicon-carbon composite negative electrode slurry.
10. The method for preparing a silicon-carbon composite negative electrode material containing a lithium-rich long-chain composite salt according to claim 9, characterized in that: The preparation method of the lithium salt comprises: reacting lithium hydroxide with an acidic solution containing a second anion group, and then extracting and purifying the resulting solution to obtain the lithium salt.
Citation Information
Cited By
Silicon-carbon composite negative electrode material containing lithium-rich long-chain composite salt and preparation method thereof
EP4507026A1